The value relevance of key audit matters and their influence on audit quality in Spain - Pais, C.; Ascenso, T. (The Tenth International Conference of the Journal of International Research, 2023)
For periods beginning on or after 17 June 2016 in the European Union, the audit report includes a new section to disclose the key audit matters (KAM), being the most significant matters in the auditor’s judgment. KAM disclosure may be value relevant and may improve audit quality, as is expected by the International Audit and Assurance Board. Thus, we study the value relevance of KAM disclosure using an event study (the absolute value of cumulative abnormal return) and two association models (the return and the price models), and the change in audit quality following KAM disclosure using as proxies earnings management and audit fees in Spanish listed firms. We do not find that KAM disclosure is value relevant or improves audit quality. These findings may be due to KAM not being important, already being known or not being understood by users and the auditor does not perform more audit work.